Differential cross sections for electron-impact excitation of laser-excited 174Yb (...6s6p 3P1) - Hein, J.; Kidwai, S.; Zetner, P.; Bostock, Christopher; Fursa, Dmitry; Bray, Igor; Sharma, L.; Srivastava, R.; Stauffer, A. (Institute of Physics Publishing Ltd., 2011)
We have measured and calculated electron-impact excitation cross sections from thelaser-excited Yb (. . . 6s6p 3P1) level to the higher-lying Yb (. . . 6s6p 1P1), (. . . 6s5d 3D1,2,3)and (. . . 6s7s 3S1) levels at 20 eV impact energy. Measurements were performed using acrossed-beam apparatus, with resonant laser radiation incident on the electron–atominteraction region, providing excited-state atomic targets. Calculations were performed in therelativistic convergent close-coupling (RCCC), convergent close-coupling (CCC), andrelativistic distorted-wave (RDW) approximations. We present measured and calculatedpartial differential cross sections (PDCS), which relate to differential cross sections andelectron-impact coherence parameters through the target state anisotropy introduced by thelaser geometry. Using theoretical predictions of the h electron-impact coherence parameter,we present the differential cross section for the 3P1–3S1 excitation.